2022
DOI: 10.48017/dj.v7i1.1713
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência do uso de micro-ondas para determinação de umidade em grãos de soja (Glycine max (l.) Merr.): Uso na radiação não-ionizante na agricultura

Abstract: Efficiency of using microwaves to determine moisture in soybeans (Glycine max (l.) Merr.)Eficiência do uso de micro-ondas para determinação de umidade em grãos de soja (Glycine max (l.) Merr.)ZOLINI, Gabriel Nunes (1) ; COSTA Thaís Ribeiro (2) ; NOBRE, Danúbia Aparecida da Costa (3) ; SILVA, Ricardo Silveira da (4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In studies developed by Nirmaan et al (2020) and Nunes-Zolini et al (2022), the microwave also showed technical feasibility for moisture determination in rice and soybean grains.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In studies developed by Nirmaan et al (2020) and Nunes-Zolini et al (2022), the microwave also showed technical feasibility for moisture determination in rice and soybean grains.…”
Section: Resultsmentioning
confidence: 92%
“…Technologies involving the adoption of microwaves to quantify the water content, require specific modeling for each species, and for accurate determination factors related to the product, such as moisture and size must be considered (RAHMAN et al, 2019;SHEN et al, 2020;SILVA et al, 2021). The adoption of a domestic microwave oven to determine the water content is already viable in studies developed by Nirmaan et al (2020) and Nunes-Zolini et al (2022). Thus, the study aimed to analyze the efficiency of using microwave oven to determine the water content in grains of peanut, sunflower, corn, soybean and wheat.…”
Section: Introductionmentioning
confidence: 99%